2013
DOI: 10.1007/s12639-013-0353-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and analysis of associated risk factors for Cryptosporidium infection in lambs in Jammu district

Abstract: An epidemiologic study was carried out to investigate the prevalence and analysis of risk of Cryptosporidium infection in lambs in Jammu district. Faecal samples of 120 lambs of different age groups viz., \1 month, 1-3 months and 3-6 months were assessed. Cryptosporidium oocysts were identified by using modified Zeihl Neelsen technique. Statistical analysis showed that infection rates were significantly higher in lambs of \1 month age group (65 %) than other two age groups (p \ 0.05). Similarly, cryptosporidia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
3
4
1
3
Order By: Relevance
“…The results also revealed that the C. parvum was equally pathogenic for both cattle (45.10%) and buffalo (38.39%) calves in all age groups, was in agreement with the finding of Maurya et al (2013). The frequency of shedding oocysts was more in diarrhoeic (59.54%) than non-diarrhoeic (29.41%) calves, the results was in agreement with finding of Maurya et al (2013) and Ahamed et al (2015). High levels of environment contamination, high output of oocysts and extensive (Masood et al, 2013).…”
Section: Comparative Evaluation Of Diagnostic Methodssupporting
confidence: 87%
“…The results also revealed that the C. parvum was equally pathogenic for both cattle (45.10%) and buffalo (38.39%) calves in all age groups, was in agreement with the finding of Maurya et al (2013). The frequency of shedding oocysts was more in diarrhoeic (59.54%) than non-diarrhoeic (29.41%) calves, the results was in agreement with finding of Maurya et al (2013) and Ahamed et al (2015). High levels of environment contamination, high output of oocysts and extensive (Masood et al, 2013).…”
Section: Comparative Evaluation Of Diagnostic Methodssupporting
confidence: 87%
“…In order not to collect feces directly from the rectum (invasive method) nor to collect feces from the floor, the animals were daily fitted with a disposable plastic bag (Ahamed et al, 2015), clearly identified with group/animal/day, allowing the feces to be stored for a maximum of 1 h before their collection in sterile boxes. This method prevents the reinfection of kids by oocysts excreted in the feces from other animals.…”
Section: Sample Collectionmentioning
confidence: 99%
“…En Turqu铆a (24) , indican en corderos de esta misma edad una prevalencia de 38.8 % (155/400), distribuida en el 90 % (18/20) de las granjas observadas, mostrando que de acuerdo con los grupos de edad, la frecuencia en corderos de una semana de edad fue 44.4 % (67/151), en corderos de dos semanas fue 37.5 % (39/104), en los de tres semanas 40 % (38/95) y 22 % (11/50) en los de cuatro semanas de edad. En la India, se identific贸 una infecci贸n de 65 % en corderos de menos de un mes de edad (25) ; en Zaragoza, Espa帽a, Cryptosporidium spp., se present贸 en corderos de 14 d铆as de edad (26) . La comparaci贸n entre estudios desarrollados en otros pa铆ses con el nuestro es dif铆cil; la informaci贸n generada en ellos permite confirmar que este par谩sito infecta con mayor frecuencia a corderos menores de 30 d铆as de edad, como se reporta en la literatura (11) , y la prevalencia es tan diversa como los sistemas de producci贸n.…”
Section: Discussionunclassified
“…Sin embargo, la edad es un factor considerado como marcador de riesgo a contraer la infecci贸n; los animales j贸venes, en especial los lactantes, son los m谩s propensos a sufrir esta enfermedad, y a ello se le adicionan al menos otros dos factores de riesgo, el estado inmunol贸gico de los animales y el manejo sanitario (25)(26)(27)(28) . La exposici贸n inicial de los neonatos a la infecci贸n ocurre en las 谩reas de parici贸n, como consecuencia de la eliminaci贸n de ooquistes por parte de las borregas gestantes; por lo general los ooquistes contaminan la ubre, el agua, el alimento y las 谩reas donde habitan los corderos; as铆, el sistema de manejo interviene en la probabilidad de transmisi贸n del protozoario entre animales infectados y susceptibles (27) .…”
Section: Discussionunclassified
See 1 more Smart Citation